2019
DOI: 10.3390/catal9040343
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design and Optimization of Triclosan and 2.8-Diclorodibenzeno-p-dioxina Degradation by the Fe/Nb2O5/UV System

Abstract: This study describes the experimental design and optimization of the photocatalytic reaction using the immobilized catalyst Fe/Nb2O5 in the degradation of Triclosan and 2.8-DCDD. The techniques employed to characterize the photocatalysts were: specific surface area, average pore volume, average pore diameter, photo-acoustic spectroscopy (PAS), X-ray diffraction (XRD), and scanning electron microscopy (SEM/EDS). The reaction parameters studied were pH, catalyst concentration, catalyst calcination temperature, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…According to the literature, the materials containing niobium pentoxide and cobalt ferrite have specific surface area BET (S BET ), Nb 2 O 5 calcined at 873 K has S BET between 22 and 57.8 mm 2 •g [50,51], without other compounds. Niobium pentoxide nanocomposites under the same temperature calcination can be S BET between 21.24 and 149.63 mm 2 •g [32,52]. Cobalt ferrite in the literature has S BET 44 mm 2 •g at 673 K, and with carbon, the shell can be S BET around 330 mm 2 •g at 773 K [53,54].…”
Section: Characterization Techniques 431 Surface and Pore Analyzermentioning
confidence: 98%
See 1 more Smart Citation
“…According to the literature, the materials containing niobium pentoxide and cobalt ferrite have specific surface area BET (S BET ), Nb 2 O 5 calcined at 873 K has S BET between 22 and 57.8 mm 2 •g [50,51], without other compounds. Niobium pentoxide nanocomposites under the same temperature calcination can be S BET between 21.24 and 149.63 mm 2 •g [32,52]. Cobalt ferrite in the literature has S BET 44 mm 2 •g at 673 K, and with carbon, the shell can be S BET around 330 mm 2 •g at 773 K [53,54].…”
Section: Characterization Techniques 431 Surface and Pore Analyzermentioning
confidence: 98%
“…Niobium pentoxide (Nb 2 O 5 ) and its combinations with other compounds have been studied as photocatalysts. Researchers report the efficiency of the photocatalytic activity of niobium oxide in the degradation of dyes in textile industries [28] and of herbicides such as methylviologen [29], as well as in the reduction of atmospheric pollution [30] and emerging pollutants [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…These phases can only be obtained from Ag and Nb 2 O 5 precursors calcined at elevated temperatures. Considering pure niobium pentoxide, Fidelis et al [19] observed that non-calcined Nb 2 O 5 samples, initially with amorphous structure, transformed into TT and T-Nb 2 O 5 crystalline phases when calcined at temperatures higher than 673 K (773-873 K). Liu et al and Chen et al, could only obtain the AgNb 13 O 33 phase after calcining their samples, respectively, at 1073 K for 3 h [20] and 1263 K for 12 h [21].…”
Section: Powder Catalystsmentioning
confidence: 99%
“…Thus, the development of efficient technologies are highly desired to remove PCPs and pharmaceuticals such as CHD from the aquatic ecosystem (Fidelis et al, 2019). Adsorption is an efficient and economical treatment for organic pollutant but with some limitations such as inefficient in complete degradation and leads to the secondary pollutant.…”
Section: Introductionmentioning
confidence: 99%